EFEKTIVITAS PELATIHAN DI WILAYAH KERJA DAN PENGARUHNYA TERHADAP KOMPETENSI PENDIDIK DAN TENAGA KEPENDIDIKAN - Abdul Kadir Ahmad; Lisa’diyah Ma’rifataini (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
The vast territory of Indonesia and the large number of employees of the Ministry of Religion who need competency improvement has an impact on the inability of the Religious Education and Training Center to provide training. Pelatihan di Wilayah Kerja (PDWK) s a solution to overcome these obstacles. This study aims to look at the process of implementing PDWK, the level of effectiveness, and its influence on the competency level of its alumni. The research method used is a combination of descriptive qualitative and quantitative data. The research was conducted in 10 Religious Training Centers, namely BDK DKI, BDK Bandung, BDK Semarang, BDK Surabaya, BDK Denpasar, BDK Makassar, BDK Manado, BDK Banjarmasin, BDK Medan, and BDK Palembang. The research results show that PDWK training has been running effectively, with improvements in several aspects. In addition, the results of this training show that the competence of alumni has increased after attending the training, the calculation results obtained a coefficient of determination = 0.521, which means that 52.1% of the competence of alumni is influenced by the effectiveness of the training and 47.9% due to other factors